MAN RESPONSIBLE - Petru ANDEA; Oana DULCA; Ioana MÎNZU (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2011)
The paper examines ways that are obtained, in higher education, professional competences as they are set in the European Qualification Framework and described through "Dublin descriptors", which examines creating and introducing ways in Romania of a national qualifications framework of Higher Education of the National Qualifications Register for Higher Education. The paper can serve for elaboration of normative acts necessary to implement the National Qualifications Framework in Higher Education (CNCIS) and the National Qualifications Register for Higher Education (RNCIS).